2016
DOI: 10.1186/s13568-016-0222-z
|View full text |Cite
|
Sign up to set email alerts
|

Prodigiosin inhibits motility and activates bacterial cell death revealing molecular biomarkers of programmed cell death

Abstract: The antimicrobial activity of prodigiosin from Serratia nematodiphila darsh1, a bacterial pigment was tested against few food borne bacterial pathogens Bacillus cereus, Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli. The mode of action of prodigiosin was studied. Prodigiosin induced bactericidal activity indicating a stereotypical set of biochemical and morphological feature of Programmed cell death (PCD). PCD involves DNA fragmentation, generation of ROS, and expression of a protein with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 21 publications
4
60
0
Order By: Relevance
“…Prodigiosin is most commonly found in environmental S. marcescens isolates and has been proposed to suppress growth of various fungi [ 47 ], bacteria [ 97 ], protozoans [ 98 ] and even viruses [ 99 ]. It has been recently suggested that prodigiosin has affinity for the lipid bilayer of the plasma membrane, causing outer membrane damage [ 100 ]. The pig operon in the S. marcescens UENF-22GI genome comprises 14 genes (Table 1 ; Additional file 1 : Figure S4) arranged in a structure that resembles the pig operon from S. marcescens ATCC274 (also an environmental isolate) [ 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…Prodigiosin is most commonly found in environmental S. marcescens isolates and has been proposed to suppress growth of various fungi [ 47 ], bacteria [ 97 ], protozoans [ 98 ] and even viruses [ 99 ]. It has been recently suggested that prodigiosin has affinity for the lipid bilayer of the plasma membrane, causing outer membrane damage [ 100 ]. The pig operon in the S. marcescens UENF-22GI genome comprises 14 genes (Table 1 ; Additional file 1 : Figure S4) arranged in a structure that resembles the pig operon from S. marcescens ATCC274 (also an environmental isolate) [ 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…We could not detect necrosis, lesions, or other phytotoxic effects, signifying that the host plant is not impaired by these metabolites. Instead, it is more likely that the host plant benefits from serratamolides and prodiginines production owing to their bioactivities 58 61 , 70 .…”
Section: Resultsmentioning
confidence: 99%
“…glutamicum . Diverse mechanisms inducing bacterial programmed cell death, including DNA intercalation, have been assigned to the pigment’s antibiotic activity [ 18 ]. For activity against Bacillus spec .…”
Section: Discussionmentioning
confidence: 99%
“…Prodigiosin, which is produced from the precursors 2-octenal and proline in a complex bifurcated pathway, has several relevant properties such as immunosuppressive and anticancer activities toward different types of human cancer cells [ 9 11 ], as well as antimicrobial effects against Gram-positive and Gram-negative bacteria [ 12 15 ]. Several molecular mechanisms causing the antibiotic effects of prodigiosin are currently discussed, e.g., membrane potential alteration via anion symport [ 16 ], membrane damage [ 15 ], phototoxicity [ 17 ], and formation of reactive oxygen species (ROS) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%